Clinical outcomes related to the incidence of ventilator-associated pneumonia in adults - a cohort study - Ariane Aparecida Viana; Déborah Maciel Cavalcanti Rosa; Alexandre Ricardo Pepe Ambrozin; Renata Croce Megna Andrade; Maurício Jamami; Bruno Martinelli (Editora Champagnat, 2018)
Abstract Introduction: Ventilator-Associated Pneumonia (VAP) is a common complication found in the Intensive Care Unit (ICU) and is associated with increased mortality, length of hospital stay and mechanical ventilation (MV) time. Objective: To determine the incidence of VAP and its impact on the clinical course of the subject undergoing invasive MV in the ICU. Methods: This is a cohort study of hospitalized subjects in the general adult ICU of the State Hospital of Bauru / SP. The clinical information for the period of 19 months were collected. Stratification for the groups was based on the presence or absence of VAP, free_VAP and VAP, respectively. The Hotelling T² with 95% confidence, chi-square and the Mann-Whitney tests were executed using the "R" software and the results showed as mean ± standard deviation and absolute and relative distribution (p < 0.05). Results: The sample was of 322 subjects; the VAP group consisted of 73 (22.67%), 54.79% male, age: 62.31±16.96 years and the APACHE II: 29.98 ± 8.64. The VAP group had longer time of the MV and of the ICU compared to free VAP group; even in this group, the highest incidence of death in the ICU occurred between the 16th and 20th day of hospitalization. The free VAP group was older and 50% of the patients discharged from hospital. Conclusion: VAP and their interfaces still impact on the clinical evolution of the subjects mainly on the time factor of MV and ICU stay. The highest incidence of death in the ICU occurs in the first weeks.